Prenatal Methamphetamine Exposure and Neonatal and Infant Neurobehavioral Outcome: Results from the IDEAL Study. Issue 1 (January 2014) - Kiblawi, Zeina N.; Smith, Lynne M.; Diaz, Sabrina D.; LaGasse, Linda L.; Derauf, Chris; Newman, Elana; Shah, Rizwan; Arria, Amelia; Huestis, Marilyn; Haning, William; Strauss, Arthur; DellaGrotta, Sheri; et al.
Background: Methamphetamine (MA) use among pregnant women is an increasing problem in the United States. How MA use during pregnancy affects neonatal and infant neurobehavior is unknown. Methods: The Infant Development, Environment, and Lifestyle (IDEAL) study screened 34, 833 subjects at 4 clinical centers. Of the subjects, 17, 961 were eligible and 3705 were consented, among which 412 were enrolled for longitudinal follow-up. Exposed subjects were identified by self-report and/or gas chromatography/mass spectroscopy (GC/MS) confirmation of amphetamine and metabolites in meconium. Comparison subjects were matched (race, birth weight, maternal education, insurance), denied amphetamine use, and had a negative meconium screen. Both groups included prenatal alcohol, tobacco, and marijuana use, but excluded use of opiates, lysergic acid diethylamide, or phencyclidine. The Neonatal Intensive Care Unit (NICU) Network Neurobehavioral Scale (NNNS) was administered within the first 5 days of life and again at 1 month to 380 enrollees (185 exposed, 195 comparison). Analysis of variance (ANOVA) tested exposure effects on NNNS summary scores at birth and 1 month. General linear model (GLM) repeated-measures analysis assessed the effect of MA exposure over time on the NNNS scores with and without covariates. Results: By 1 month of age, both groups demonstrated higher quality of movement ( P = .029), less lethargy ( P = .001), and fewer asymmetric reflexes ( P = .012), with no significant differences in NNNS scores between the exposed and comparison groups. Over the first month of life, arousal increased in exposed infants but decreased in comparison infants ( P = .031) and total stress was decreased in exposed infants, with no change in comparison infants ( P = .026). Conclusions: Improvement in total stress and arousal were observed in MA-exposed newborns by 1 month of age relative to the newborn period.